Microscale thermal management: A review of nanofluid applications in microfluidic channels - Samylingam, Lingenthiran; Aslfattahi, Navid; Kadirgama, Kumaran; Ramasamy, Devarajan; Norazlianie, Sazali; Wan Sharuzi, Wan Harun; Kok, Chee Kuang; Nor Atiqah, Zolpakar; Mohd Fairusham, Ghazali (ETASR, 2024)
This critical review study focuses on the integration of nanofluids with microfluidic channels. This emerging field, which combines nanotechnology and microfluidics, has the potential to transform the control of temperatures and monitoring completely. Nanofluids, which are fluids containing nanoparticles like metals or oxides, greatly improve the heat management capabilities of base fluids. These materials are highly efficient in transferring and conducting heat, making them ideal for applications such as cooling electronics and medical diagnostics. The addition of nanofluids to microfluidic routes, typically measured in micrometers, greatly simplifies fluid flow and heat transfer regulation. The article includes several research studies demonstrating how nanofluids enhance the performance of microfluidic systems compared to conventional fluids. The benefits are examined, including the potential for reduced size and increased energy efficiency of heat exchanges and cooling systems. As a result, these technologies are better suited for implementation in the healthcare and industry sectors.